Clostridium difficile Infection Is Associated With Poor Outcomes in End-Stage Renal Disease. (1st February 2012) - Pant, Chaitanya; Deshpande, Abhishek; Anderson, Michael P.; Sferra, Thomas J.
Abstract : Objective: To investigate the association of Clostridium difficile infection (CDI) with the outcomes of hospitalized patients with end-stage renal disease (ESRD). Methods: We extracted all adult cases with a discharge diagnosis of ESRD or CDI from the United States Nationwide Inpatient Sample 2009 database. Outcome variables (mortality, length of hospital stay [LOS], and hospitalization charges), demographic information, and comorbidity data were collected. Data were evaluated by univariate and multiple regression analyses. Results: We identified 184, 139 cases with ESRD of which 2.8% had CDI. Comparison of patients with ESRD + CDI to those with only ESRD revealed in-hospital mortality (13.2% vs 5.3%; P < 0.001), LOS (17.3 vs 7.1 days; P < 0.001), and charges ($124, 846 vs $56, 663; P < 0.001) to be more than 2-fold greater. In the ESRD cohort (ESRD only and ESRD + CDI), CDI was independently associated with greater mortality (adjusted odds ratio, 2.15; 95% CI, 2.07–2.24; P < 0.001), longer LOS (mean difference, 9.4 days; 95% CI, 9.2–9.5; P < 0.001), and higher charges (mean difference, $62, 824; 95% CI, 61, 615–64, 033; P < 0.001). Conclusions: Clostridium difficile infection is associated with significantly worse outcomes in hospitalized patients with ESRD.